1996
DOI: 10.1136/vr.138.25.615
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of morbillivirus infection in polar bears (Ursus maritimus) from Alaska and Russia

Abstract: One-hundred-and-ninety-one samples of blood serum collected from 186 polar bears (Ursus maritimus) between 1987 and 1992 were analysed for morbillivirus antibodies. The samples were collected in the Bering, Chukchi and East Siberian seas. Sixty-eight samples (35.6 per cent) had morbillivirus antibody titres > 5; the percentage of positive samples ranged from 26.2 to 46.2 per cent from year to year. The proportions of adults, sub-adults and cubs which were seropositive were 43.9, 35.7 and 37.9 per cent respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 22 publications
(26 reference statements)
0
21
1
Order By: Relevance
“…Antibody prevalence in polar bears from the Chukchi Sea population was also greater in adults than in juveniles and similar between sexes (Follmann et al, 1996), but antibody prevalence in juveniles was higher than that found in the present study (ϳ37% vs. 5% for both Canadian populations). Although the significance of this difference is unknown, it is important to note that the number of samples available for serology from juvenile bears in the present study was small (22 out of 200 samples) and was therefore possibly too few to estimate prevalence accurately.…”
Section: )contrasting
confidence: 55%
See 3 more Smart Citations
“…Antibody prevalence in polar bears from the Chukchi Sea population was also greater in adults than in juveniles and similar between sexes (Follmann et al, 1996), but antibody prevalence in juveniles was higher than that found in the present study (ϳ37% vs. 5% for both Canadian populations). Although the significance of this difference is unknown, it is important to note that the number of samples available for serology from juvenile bears in the present study was small (22 out of 200 samples) and was therefore possibly too few to estimate prevalence accurately.…”
Section: )contrasting
confidence: 55%
“…Furthermore, repeated exposure seems unlikely, given that nine bears tested seronegative at first capture and remained seronegative up to 5 yr later. This persistence of antibody titers was also observed in some bears from the Chukchi Sea population over a period of 2 yr (Follmann et al, 1996). However, antibody titers may not always persist-one bear from each of the Chukchi Sea and WH populations tested seropositive at first capture but seronegative at second capture.…”
Section: )mentioning
confidence: 85%
See 2 more Smart Citations
“…4,9,11,12,20,30 Sources of confusion regarding the host range of CDV in felids have arisen from disparate reports of the lack of CDV disease in domestic cats and the occurrence of fatal CDV-like disease in captive and free-roaming large felids. 4,[8][9][10][26][27][28]31,34,37,45 The debate regarding CDV interspecies transmission (canid to felid) versus the existence of a unique feline morbillivirus strain antigenically related to CDV has not been fully resolved.…”
mentioning
confidence: 99%